Teori Konstruktivisme dalam Pembelajaran: Tinjauan Pendidikan Agama Islam - Nabila Raessal Manda Putri; Asa Mega Nusantara; Retno Pangestuti (IAIN Datuk Laksemana Bengkalis, Indonesia, 2025)
This article examines the application of the constructivist approach in Islamic Religious Education learning in the context of the 21st century, which is characterized by rapid technological advances, Artificial Intelligence (AI), globalization, and the characteristics of Generation Z and Generation Alpha students. The issue raised is that Islamic Religious Education learning is still predominantly knowledge transfer-oriented, making it less meaningful and less relevant to the reality of students. The research uses a descriptive qualitative approach with a literature study method through an analysis of literature related to constructivism and Islamic Religious Education learning design. The results of the study show that constructivism encourages more active and contextual Islamic Religious Education learning through problem-based activities, collaborative discussions, reflection, and gradual support (scaffolding) towards independent learning. The implication is that teachers act as facilitators who guide inquiry and the application of values so that the internalization of Islamic teachings is reflected in attitudes and behavior. This article recommends strengthening the pedagogical competence of PAI teachers, implementing active learning models, and using authentic assessments to evaluate cognitive, affective, and psychomotor achievements in a balanced manner.